Pemahaman Hermeneutik terhadap 1 Korintus 10:13: Analisis atas Kesalahpahaman dalam Tradisi Kristen Masa Kini - Wennar, Wennar; Runesi, Leonardus; Ronal, Ronal (Pusat Studi Pentakosta Indonesia, 2025)
Misinterpretations of 1 Corinthians 10:13 are common in the modern Christian tradition, especially when the verse is understood as a guarantee of total freedom from suffering. An overly literal interpretation of the phrase